(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Jaishree Mishra projects herself as an ideal spokesperson as well as the representative of the women folk of the current time. The literary career of her took off with the very popular novel Ancient Promises that was released in 2000. The author’s primary focus is actually on the struggles of women. Women’s in her novels appear to be a personification of contemporary women who could be in a position to deal with the burden of inhibition they’ve carried from generation to generation. The household setup of all heroines of Misra is strictly patriarchal. Domestic violence is portrayed perfectly in the novel. This particular article is designed to analyse as well as determine the idea of’ New Woman’ in the novels of Jaishree Misra. The study additionally seeks to trace the journey of the’ new woman’ tracing her’ self’ at various phases of life.